Overt social support behaviors : Associations with PTSD, concurrent depressive symptoms and gender - Crevier, Myra G. (2014)
Women are twice as likely as men to develop a posttraumatic stress disorder (PTSD). Gender differences in social support after a traumatic event might partially explain this disparity. However, the portrait of the links among PTSD, depression, social support, and gender is still unclear. This study examined behaviors of individuals with PTSD and their significant other in relation to PTSD and concurrent depressive symptoms, and tested gender as a moderator of these associations. Observed overt supportive and countersupportive behaviors of 68 dyads composed of an individual with PTSD and a significant other in a trauma-oriented discussion were coded with a support coding system and analyzed according to gender. Gender was revealed to act as a moderator of the links between interactional behaviors of individuals with PTSD and their concurrent depressive symptoms. More specifically, women were less implicated and less likely to propose positive solutions compared with men. On the other hand, men were more implicated and less likely to criticize their significant other than were women. PTSD and concurrent depressive symptoms were related to poorer interpersonal communication in women. Hence, women and men with PTSD and concurrent depressive symptoms might benefit from gender-tailored interventions targeting symptoms and dyadic behaviors